Phytochemical Investigation and in vitro Antimicrobial and Antioxidant Activities Evaluation of Erianthemum aethiopicum Wiens and Polhill - Gonfa T; Temesgen A; Kiros T; Muthusaravanan S; Erba Urgessa O; Teklu T (Journal of Experimental Pharmacology, 2024)
Teshome Gonfa,1 Ayalew Temesgen,1 Tsegu Kiros,1 Sivasubramanian Muthusaravanan,1 Olyad Erba Urgessa,2 Tadele Teklu2 1Department of Chemistry, College of Natural and Computational Sciences, Haramaya University, Dire Dawa, Ethiopia; 2School of Biological Sciences and Biotechnology, College of Natural and Computational Sciences, Haramaya University, Dire Dawa, EthiopiaCorrespondence: Teshome Gonfa; Tsegu Kiros, Department of Chemistry, Haramaya University, P. O. Box: 138, Dire Dawa, Oromia, Ethiopia, Tel +251936566688, Email tashe2002@gmail.com; kirosorg@gmail.comBackground: Erianthemum aethiopicum Wiens and Polhill (Loranthaceae) is a parasitic plant native to north eastern Africa and Ethiopia. In Ethiopia, it is traditionally used to treat breast swelling, mastitis, morning illnesses and vomiting.Objective: This study aimed to screen the main phytochemical constituents; determine the total amounts of phenolics, flavonoids, and tannins; and evaluate the antimicrobial (against Escherichia coli, Staphylococcus sciuri, Candida glaebosa and Cryptococcus albidus) and antioxidant (against DPPH radical and ferric ion) activities of E. aethiopicum leaves extracts.Methods: Powdered E. aethiopicum leaves were macerated using n-hexane, chloroform, ethyl acetate, ethanol, and methanol. All crude extracts were qualitatively screened for phytochemical identification. The total phenolic, flavonoid, and condensed tannin contents of the chloroform, ethanol, and methanol extracts were determined by UV-Vis spectrophotometry. The n-hexane, chloroform, and methanol extracts were evaluated for their antimicrobial activity against the aforementioned microbes using agar disc diffusion and broth micro-dilution techniques. Chloroform, ethanol, and methanol extracts were also evaluated for antioxidant activity by DPPH and ferric ion reduction antioxidant power (FRAP) assays.Results: Methanol (17.56 ± 16%) and ethanol (16.45 ± 19%) showed better extraction efficiency. Flavonoids, polyphenols, tannins, terpenoids, saponins, and sterols were detected in all extracts. The highest total content of phenolics (22.63 ± 0.69 mgGAE/gDCE), flavonoids (5.38 ± 0.52 mgCE/gDCE) and tannins (39.18 ± 38 mg CE/g DCE), as milligram of gallic acid and catechin per gram of dried crude extract, were recorded in the methanolic extract. The methanolic extract also presented best anti -DPPH strength (IC50, 4.31 μg/mL) and ferric ion reduction power (absorbance of 0.71) though found weak compared to the ascorbic acid (IC50 of 0.49 μg/mL and absorbance of 0.93, respectively).Conclusion: All evaluated extracts displayed antifungal activity against both Cryptococcus albidus and Candida glaebosa strains (minimum inhibitory concentration values of 12.5– 25 mg/mL), whereas they were found to have negligible activity against all tested bacterial strains. This report provides preliminary information for further phytochemical investigation of Erianthemum aethiopicum to isolate potential antioxidant and antifungal compounds.Keywords: Erianthemum aethiopicum, antimicrobial assay, DPPH assay, FRAP assay, phytochemical analysis, minimum inhibitory concentration